The dispute about human nature. Comments on the concept of human nature in the context of transhumanism and biotechnological enhancements. - Lagos Berríos, Rodrigo (Revista Ethika+, 2022)
The advance of biotechnologies, genetic engineering, and synthetic biology has made it possible to alter and modify the capabilities of human beings at will. In this context, a debate arises between transhumanists and bioconservatives as to whether the enhancement of human beings through biotechnologies is desirable or whether so-called human nature should be protected as the basis of rights, values, and moral precepts. The following paper is concerned with analyzing the concept of human nature, which is at the center of this discussion, and asks whether it is an adequate criterion for drawing moral indications for restricting biotechnological improvements in human beings.